2023
DOI: 10.3324/haematol.2022.282394
|View full text |Cite
|
Sign up to set email alerts
|

TIM3, a human acute myeloid leukemia stem cell marker, does not enrich for leukemia-initiating stem cells in B-cell acute lymphoblastic leukemia

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…T‐cell immunoglobulin mucin‐3 (Tim‐3) is a transmembrane protein belonging to the TIM family that is expressed on almost all forms of AML primitive cells but not on HSCs, making it a promising target 82 . The main cause of leukaemia relapse after chemotherapy is resistance to LSCs because they cannot target the elimination of LSCs.…”
Section: Different Targets Of Car‐t For Amlmentioning
confidence: 99%
See 1 more Smart Citation
“…T‐cell immunoglobulin mucin‐3 (Tim‐3) is a transmembrane protein belonging to the TIM family that is expressed on almost all forms of AML primitive cells but not on HSCs, making it a promising target 82 . The main cause of leukaemia relapse after chemotherapy is resistance to LSCs because they cannot target the elimination of LSCs.…”
Section: Different Targets Of Car‐t For Amlmentioning
confidence: 99%
“…T‐cell immunoglobulin mucin‐3 (Tim‐3) is a transmembrane protein belonging to the TIM family that is expressed on almost all forms of AML primitive cells but not on HSCs, making it a promising target. 82 The main cause of leukaemia relapse after chemotherapy is resistance to LSCs because they cannot target the elimination of LSCs. In one study, researchers created a phage library from which anti‐human TIM antibodies were isolated and evaluated the killing ability of second‐generation TIM3 CAR‐T cells against leukaemia cell lines and primary AML cells in vitro and found that they had good anti‐leukaemia activity.…”
Section: Different Targets Of Car‐t For Amlmentioning
confidence: 99%